Characterization of phenolic compounds in flowers of wild medicinal plants from Northeastern Portugal. - Barros, Lillian (2012)
Crataegus monogyna, Cytisus multiflorus, Malva sylvestris and Sambucus nigra have been used as important medicinal plants in the Iberian Peninsula since a long time ago, and are claimed to have various health benefits. This study aimed to determine the phenolic profile and composition of wild medicinal flowers of those species. The analysis was performed by HPLC-DAD-ESI/MS. Flavonoids, and particularly flavonols and flavones, were the main groups in almost all the studied samples. C. multiflorus sample gave the highest levels of total flavonoids (54.5 mg/g dw), being a chrysin derivative the most abundant flavone found (22.3 mg/g dw). C. monogyna revealed the highest concentration in phenolic acids (5.5 mg/g dw) that were not found in C. multiflorus sample; 5-O-caffeoylquinic acid was the most abundant phenolic acid found in the first species, being a procyanidin trimer also found (1.4 mg/g dw). Kaempferol-3-O-rutinoside (0.84 mg/g dw) and quercetin-3-O-rutinoside (14.9 mg/g dw) were the main flavonols present in M. sylvestris and S. nigra, respectively. Due to the well established antioxidant activity of phenolic compounds, the studied wild medicinal flowers could be selected for processing extracts with health-promoting properties or to be incorporate into functional beverages or products with bioactive properties related to oxidative stress.